You Are the Future: Embodied History in China's Psy‐boom. (16th June 2020) - Shoemaker, Barclay Bram
Abstract: Ms. Zhou, Ms. Liu, and Ms. Wen represent three generations of psychological counselors in China. They all work in Chengdu, the provincial capital of Sichuan province. China is in the midst of what scholars call the "psy‐boom." This is generally defined as the rapid rise in psychological services in the country. Rather than understanding this rise as a linear phenomenon or one in which the understanding of psychology and its uses are universally shared by all practitioners, these three therapists show how haphazard and staggered the uptake in psychological services has been. They also show how the different historical contexts and shifting qualification standards that defined their generation of the psy‐boom in turn shaped their therapeutic practice. The study uses Bourdieu's concept of the habitus to show how the embodied history of China's psy‐boom impacts the practice of counselling and understanding of psychology.